Societal institutions and control system characteristics: empirical evidence from the UAE. Issue 2 (14th September 2015) - Youssef, Mayada Abd El-Aziz; Moustafa, Essam
Abstract : Purpose: – This paper aims to explore the existence of two sets of factors societal institutions and management control systems' (MCS) characteristics in the UAE business entities. Subsequently, this paper empirically examines the bilateral and the multivariate associations between the two sets. The societal institutions include six factors categorised in three main groups: cultural conventions, state structures and policies and skill development and control. The MCS characteristics consist of four factors which are: reliance on formal rules, control over the behaviour of employees, involvement of subordinates in target setting and performance evaluation and scope of information used in performance evaluation. Design/methodology/approach: – Whitley's model (1999) is adopted in the UAE business environment and the analyses are performed at the organisational level. Qualified accounting officials and managers are surveyed. The Kruskal-Wallis test, Spearman's partial correlation and multiple regression are used for data analyses. Findings: – Findings reveal the characteristics of the UAE societal institutions and the MCS in UAE organisations. They also reveal significant associations among four of the societal institution factors and most of the MCS characteristics. The results highlight the role played by the government structures and policies group in influencing the MCS characteristics in the UAE organisations. However, these results do not entirely agree with Whitley's model. Research limitations/implications: – The results of this study are restricted by the typical constraints associated with the survey method. The obtained results have implications for researchers and managers in facilitating the understanding of the relations among the various societal institutions and the MCS characteristics. Originality/value: – This research, to the best of the authors' knowledge, provides significant new empirical evidence into the relation between societal institutions and MCS characteristics in a non-Western economy.